Spatial and temporal distribution of Taenia solium and its risk factors in Uganda - Ngwili, Nicholas; Sentamu, Derrick N.; Korir, M.; Adriko, M.; Beinamaryo, P.; Dione, Michel M.; Kaducu, J.M.; Mubangizi, A.; Mwinzi, P.N.; Thomas, Lian F.; Dixon, M.A. (Elsevier, 2023)
Background The lack of sub-national mapping of the zoonotic cestode Taenia solium in endemic countries presents a major challenge to achieving intensified T. solium control milestones, as outlined in the “World Health Organization neglected tropical disease roadmap by 2030”. We conducted a mapping study in Uganda, considered to be endemic, to identify sub-national high-risk areas.